Rpv29, Rpv30 and Rpv31: Three Novel Genomic Loci Associated With Resistance to Plasmopara viticola in Vitis vinifera - Sargolzaei, Maryam; Maddalena, Giuliana; Bitsadze, Nana; Maghradze, David; Bianco, Piero Attilio; Failla, Osvaldo; Toffolatti, Silvia Laura; De Lorenzis, Gabriella (Frontiers in Plant Science, 2020)
Plasmopara viticola (Berk. et Curt.) Berl. and de Toni, the agent of downy mildew, is one of the most important pathogens of European grapevine (Vitis vinifera L.). Extensive evaluation of cultivated grapevine germplasm has highlighted the existence of resistant phenotypes in the Georgian (Southern Caucasus) germplasm. Resistance is shown as a reduction in disease severity. Unravelling the genetic architecture of grapevine response to P. viticola infection is crucial to develop resistant varieties and reduce the impact of disease management. The aim of this work was to apply a genome-wide association (GWA) approach to a panel of Georgian-derived accessions phenotyped for P. viticola susceptibility and genotyped with Vitis18kSNP chip array. GWA identified three highly significant novel loci on chromosomes 14 (Rpv29), 3 (Rpv30) and 16 (Rpv31) associated with a low level of pathogen sporulation. Rpv29, Rpv30 and Rpv31 loci appeared to be associated with plant defense genes against biotic stresses, such as genes involved in pathogen recognition and signal transduction. This study provides the first evidence of resistant loci against P. viticola in V. vinifera germplasm, and identifies potential target genes for breeding P. viticola resistant grapevine cultivars.